A novel fabrication methodology for sulfur-doped ZnO nanorods as an active photoanode for improved water oxidation in visible-light regime. (28th December 2016) - Khan, A; Ahmed, M I; Adam, A; Azad, A-M; Qamar, M
Abstract: Incorporation of foreign moiety in the lattice of semiconductors significantly alters their optoelectronic behavior and opens a plethora of new applications. In this paper, we report the synthesis of sulfur-doped zinc oxide (S-doped ZnO) nanorods by reacting ZnO nanorods with diammonium sulfide in vapor phase. Microscopic investigation revealed that the morphological features, such as, the length (2–4 μ m) and width (100–250 nm) of the original hexagonal ZnO nanorods remained intact post-sulfidation. X-ray photoelectron spectroscopy analysis of the sulfide sample confirmed the incorporation of sulfur into ZnO lattice. The optical measurements suggested the extension of absorption threshold into visible region upon sulfidation. Photoelectrochemical (PEC) activities of pure and S-doped ZnO nanorods were compared for water oxidation in visible light ( λ  > 420 nm), which showed several-fold increment in the performance of S-doped ZnO sample; the observed amelioration in the PEC activity was rationalized in terms of preferred visible light absorption and low resistance of sulfide sample, as evidenced by optical and electrochemical impedance spectroscopy.